The influence of local non-farm employment on rural household structure in Northeast Thailand. (August 2017) - Shirai, Yuko; Fox, Jefferson; Leisz, Stephen J.; Fukui, Hayao; Rambo, A. Terry
Abstract: This paper examines how the structure of rural households in Northeast Thailand is influenced by the availability of local non-farm employment opportunities. It compares the frequency of different types of households (i.e., nuclear, extended, skipped generation, and truncated households) in two villages that were similar in most respects but differed in the shares of households with members having local non-farm employment. Almost three-quarters of all households in the village with a large share of households having members with local non-farm employment were of the extended and nuclear types. In the village with a small share of households having members with such employment, half of all households were of the skipped generation and truncated types. The extent of out-migration of young adult villagers seeking jobs in large cities also varied according to the availability of local non-farm employment. The village where many households have members with local non-farm employment had a smaller number of out-migrants. This contributes to its having more extended and nuclear households and fewer skipped generation and truncated households than the village with a greater number of out-migrants. These findings suggest that, in an area undergoing rapid economic development and modernization, rural household structure is strongly influenced by specific local economic conditions, in this case the availability of non-farm employment, rather than resulting from a universal trend toward the dominance of nuclear households as posited by convergence theory. Highlights: Local non-farm employment strongly influences rural household structure and out-migration. Extended and nuclear households are predominant in villages with high local employment rates. Skipped generation and truncated households are common in villages with limited local employment.